Composição química e bromatológica de Egeria densa, Egeria najas e Ceratophyllum demersum - Corrêa, M.r. [UNESP]; Velini, E.d. [UNESP]; Arruda, D.p. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2003)
The purpose of this work was to evaluate the chemical and bromatological composition of three submerged aquatic plant species originated from mechanical control operations, to later determine the best strategy to discard and/or use the biomass harvested during the mechanical control operations. This study was carried out in the summer and winter of 2001, with the plants being harvested at nine points on Tietê River of the Jupia reservoir. Samples were dried, milled and sent for analysis. Among the three species, the highest concentration of the analyzed elements was observed in plants harvested during the summer with a decrease in concentration being observed in plants harvested in the winter. C. demersum showed the best bromatological concentration with higher rates of crude protein, minerals and digestibility.

O objetivo deste trabalho foi avaliar a composição química e bromatológica de três espécies de plantas aquáticas imersas provenientes de operações de controle mecânico, para, posteriormente, determinar a melhor estratégia para descarte e/ou aproveitamento da biomassa coletada nestas operações. O estudo foi realizado no verão e inverno de 2001, sendo realizadas coletas em nove pontos da porção Tietê do reservatório de Jupiá. As amostras foram desidratadas, moídas e encaminhadas aos laboratórios para análise. Para as três espécies, a maior concentração dos elementos analisados foi observada em plantas coletadas durante o verão, com certo declínio nas concentrações nas plantas coletadas no inverno. C. demersum mostrou melhor constituição bromatológica, com índices superiores de proteína bruta, minerais e digestibilidade.
Chemical and bromatological composition of Egeria densa, Egeria najas and Ceratophyllum demersum
Keywords: mechanical control; discard; aquatic macrophytes; controle mecânico; descarte; macrófitas aquáticas